11/x=-5/3x+1

Simple and best practice solution for 11/x=-5/3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11/x=-5/3x+1 equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

11/x = (-5/3)*x+1 // - (-5/3)*x+1

11/x-((-5/3)*x)-1 = 0

(5/3)*x+11/x-1 = 0

5/3*x^1+11*x^-1-1*x^0 = 0

(5/3*x^2-1*x^1+11*x^0)/(x^1) = 0 // * x^2

x^1*(5/3*x^2-1*x^1+11*x^0) = 0

x^1

(5/3)*x^2-x+11 = 0

(5/3)*x^2-x+11 = 0

DELTA = (-1)^2-(4*11*(5/3))

DELTA = -217/3

DELTA < 0

x in { }

x belongs to the empty set

See similar equations:

| 5g+2(-6+4g)=1-g | | 7x^2-3x+3=0 | | -4x^2-20x-15=0 | | 4y+2=30 | | (3w-8)(6-w)=0 | | 3x+7=3x-9 | | 2/3x+3/4x=-34 | | 3(0.6+0.8y)+2y=4 | | n=(3)-7 | | 8(x-6)=5x+3(x-16) | | c=.25m(r+z) | | 1/1+1/a/1/1-1/a | | 11t+3t-5= | | 7x+-2(x+-5)=3(x+-2)+-5x | | 3/4=4x-5/6 | | .2(x+5)=x+5 | | x+4=(x-4)2 | | z^2-7=-30 | | 3/4=4x-5 | | 3[z-(3z+18)+8]=5(z+5) | | 5(.666y+1.333)-4y=3 | | (4x-5/2)-(2x-1/6)=x | | 16x+24=7[x+6] | | (.6)y-4(9)=3-2y | | 32+2y=4 | | 3(15)+x=54 | | 54+6x+4(54-3x)=180 | | 2(z+1)-(5z-4)= | | (19b-6)-9(2b+4)=-2 | | 2(2)y+1=(2)y+3 | | 9x-8=16x+27 | | 12x+2.6=6.8x |

Equations solver categories